Sistem Pendukung Keputusan Menentukan Siswa Terbaik di SMK Arkid Madani Menggunakan Metode VIKOR - Tata Andriansyah; Ayu Mira; zaenal Hakim (SITUSTIKA FIKUNMA, 2023)
The problem in this study is that the process of selecting the best students at SMK Arkid Madani currently still has obstacles or problems, including the process of selecting students is still semi-manual data and the best student data is still archived manually not based on a system that can be scattered and also causes the archive to be lost, thus hampering the selection of the best students at SMK Akrid Madani. The selection process is so strict but not effective and efficient that the selection of the best students at SMK Akrid Madani does not always run smoothly. The purpose of this study is to help makedecisions in providing selection results for determining the best students at SMK Arkid Madani who are efficient, effective and professional in determining the recipients of the bestv students, this system can be accessed easily through a Web browser. This study uses the Visekriterijumsko Compromise Method (VIKOR) which is one of the multi-criteria decision-making methods based on the concept of outranking using pairwise comparisons of alternatives based on appropriate criteria, and the results of this study produce a Decision Support System Determines the Best Students at SMK Arkid Madani Using the VIKOR Method.